Monkeypoxvirus (MPXV) in a Baby Monkey - Molecular Investigation - Orta, Yakup Sinan; Kale, Mehmet; Özmen, Özlem; Usta, Ayşegül; Koçlu, Ozan; Yıldırım, Yakup (Acta Scientiae Veterinariae, 2023)
Background: Monkeypox is a zoonotic virus that transmits from animal to human and human to human. Despite the fact that the Monkeypox virus (MPXV) was initially isolated in 1958 and the first human case was reported in 1970, thousands of cases have been documented in European countries, the United States, and Turkey in recent years. The goal of this work was to present the results of the first molecular diagnostic analysis of MPXV-induced skin lesions in a baby monkey in Turkey. Case: In 2019, a baby monkey in Antalya Zoo developed skin lesions after being brought from Africa by a female monkey. The baby monkey died within a few weeks due to postnatal respiratory problems. Skin lesions were taken from this case and analyzed molecularly and virologically at the Department of Pathology, Burdur Mehmet Akif Ersoy University Faculty of Veterinary Medicine, and the Department of Virology. To perform molecular diagnosis, skin and pock lesions developed after inoculation on the chorioallantoic membrane (CAM) of the embryonated chicken eggs (ECE) were extracted, and 25 parapoxvirus (orf virus) type-specific primers and 2 MPXV type-specific primers were examined. The inoculum was prepared from the skin lesions for virus isolation, which was carried out in Vero cell culture. Then, the virus titer was determined using the microtitration method. The polymerase chain reaction (PCR) test with 25 parapoxvirus (orf virus) type-specific primers on the extracted skin lesion samples did not detect the presence of viral genome. The presence of viral genome was detected in 1 of the 2 MPXV type-specific primers acidophilic-type inclusion body (ATI gene) in the skin lesion extracts. However, the presence of viral genome could not be determined by the Gabon (1/2) primers. Cytopathological effects (CPE) were observed 72 h. after inoculating the skin lesion inoculum in Vero cells. The virus titer was determined to be 1022 TCID50 /mL. During immunohistochemical examination with orf virus antibodies, positive reaction was observed in the epidermal cells. Discussion: The researchers have been investigated the reservoir or natural hosts of MPXV. The virus has been found in squirrels, rodents, monkeys and chimpanzees. Multiple examinations have revealed that a number of animal species, primarily rodents and nonhuman primates, are susceptible to the virus. The presence of MPXV was detected in the skin lesion of a baby monkey in the study. Capripoxvirus, Cervidpoxvirus, Avipoxvirus, Molluscipoxvirus, Orthopoxvirus, Leporipoxvirus, Suipoxvirus, Yatapoxvirus, and Parapoxvirus are all members of the Chordopoxvirinae subgroup. However, no relationship between MPXV and parapoxvirus (25 type-specific primers) was found in the extracted skin lesion samples. Virus isolation, electron microscopy, (PCR), IgM and IgG ELISA, immunofluorescence assays, and histopathological examination are all laboratory diagnostic procedures that can be used to diagnose monkeypox infections. To detect the MPXV agent and/or specific viral DNA sequences, real-time or traditional PCR techniques should be utilized. Hemagglutinin, ATI gene, and the crmB gene are all MPXV genes which are commonly used for conventional PCR testing. A MPXV type-specific primer (ATI gene) observed the presence of viral genome in the skin lesion extract. After inoculating the skin lesion inoculum in Vero cells, (CPE) were observed. The virus titer was found to be extremely high. Positive reactions were seen in epidermal cells during immunohistochemical testing with orf virus antibodies. Keywords: Monkeypox virus, molecular diagnosis, virological diagnosis, immunohistochemistry, Parapoxvirus.